2015
DOI: 10.3389/fpls.2015.00816
|View full text |Cite
|
Sign up to set email alerts
|

Ion and lipid signaling in apical growth—a dynamic machinery responding to extracellular cues

Abstract: Apical cell growth seems to have independently evolved throughout the major lineages of life. To a certain extent, so does our body of knowledge on the mechanisms regulating this morphogenetic process. Studies on pollen tubes, root hairs, rhizoids, fungal hyphae, even nerve cells, have highlighted tissue and cell specificities but also common regulatory characteristics (e.g., ions, proteins, phospholipids) that our focused research sometimes failed to grasp. The working hypothesis to test how apical cell growt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 52 publications
1
2
0
Order By: Relevance
“…The guanylyl cyclase domain of DGK4 has also been suggested to modulate NO responses (Wang et al ., ; Wong et al ., ), thus providing a link between NO and Ca 2+ signalling. Both second messengers are involved in tube guidance (Domingos et al ., ; Malhó et al ., ), and our data support such a hypothesis with dgk4 mutant tubes exhibiting altered mechanical properties and reduced ability to target the ovaries. Our qPCR data also showed that dgk4 mutant pollen has downregulation of CAP1, a cyclase‐associated protein in which a mutation was reported to reduce pollen tube length and disrupt actin filaments (Deeks et al ., ).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The guanylyl cyclase domain of DGK4 has also been suggested to modulate NO responses (Wang et al ., ; Wong et al ., ), thus providing a link between NO and Ca 2+ signalling. Both second messengers are involved in tube guidance (Domingos et al ., ; Malhó et al ., ), and our data support such a hypothesis with dgk4 mutant tubes exhibiting altered mechanical properties and reduced ability to target the ovaries. Our qPCR data also showed that dgk4 mutant pollen has downregulation of CAP1, a cyclase‐associated protein in which a mutation was reported to reduce pollen tube length and disrupt actin filaments (Deeks et al ., ).…”
Section: Discussionsupporting
confidence: 84%
“…). Such fluctuations are consistent with a protein role in signalling networks and secretory events (Odorizzi et al ., ; Malhó et al ., ; Bloch et al ., ).…”
Section: Resultsmentioning
confidence: 99%
“…The regulatory mechanisms of tip growth have been extensively investigated using root hairs and pollen tubes as single-cell models. These mechanisms involve ion flux, the asymmetric distribution of F-actin, phosphoinositides, membrane trafficking of membrane and cell wall materials, the production of reactive oxygen species, and plant hormones [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%